The Impacts of Medicaid Expansion on Rural Low-Income Adults: Lessons From the Oregon Health Insurance Experiment. (June 2018) - Allen, Heidi; Wright, Bill; Broffman, Lauren
Medicaid expansions through the Affordable Care Act began in January 2014, but we have little information about what is happening in rural areas where provider access and patient resources might be more limited. In 2008, Oregon held a lottery for restricted access to its Medicaid program for uninsured low-income adults not otherwise eligible for public coverage. The Oregon Health Insurance Experiment used this opportunity to conduct the first randomized controlled study of a public insurance expansion. This analysis builds off of previous work by comparing rural and urban survey outcomes and adds qualitative interviews with 86 rural study participants for context. We examine health care access and use, personal finances, and self-reported health. While urban and rural populations have unique demographic profiles, rural populations appear to have benefited from Medicaid as much as urban. Qualitative interviews revealed the distinctive challenges still facing low-income uninsured and newly insured rural populations.